Seed endophytic ammonia oxidizing bacteria in Elymus nutans transmit to offspring plants and contribute to nitrification in the root zone - Liang, Danni; Bowatte, Saman (Frontiers in Microbiology, 2022)
Ammonia oxidising bacteria (AOB) in soil are of great biological importance as they regulate the cycling of N in agroecosystems. Plants are known to harbour AOB but how they occupy the plant is an unresolved question. Here, we carried out metabarcoding studies using Illumina MiSeq sequencing to test the potential of seed-vectored AOB exchange between plants and soil. We found 27 sequences associated with AOB strains belonging to the genera Nitrosospira, Nitrosovibrio and Nitrosomonas inhabiting Elymus nutans seeds collected from four geographically distanced alpine meadows. Nitrosospira multiformis was the most dominant across the four locations. The AOB community in E. nutans seeds was compared with that of the leaves, roots and soil in one location. Soil and seeds harboured a rich but dissimilar AOB community, and Nitrosospira sp. PJA1, Nitrosospira sp. Nsp17 and Nitrosovibrio sp. RY3C were present in all plant parts and soils. When E. nutans seeds were germinated in sterilized growth medium under greenhouse conditions, the AOB in seeds later appeared in leaves, roots and growth medium, and contributed to nitrification. Testing the AOB community of the second-generation seeds confirmed vertical transmission, but low richness was observed. These results suggest seed-vectored AOB may play a critical role in N cycle.